Resource mobilisation and economic development in Nepal during the plan period - Jha, Hari Bansh (Allahabad, 1984)
The book reveals various constraints in the process of reso urce mobilisation and consequently unsatisfactory pace of economic development of the country. The test of the different development models in the conditions of the Nepalese economy indicates that capital accumulation is essential beyond any measure for the rapid development of the country. An in depth study has, therefore, been conducted to increase the quantum of capital accumulation and to mobilise financial resources both from within and outside the country to the maximum possible extent. In this connection, efforts have been made to identify the problems and mobilise additional resources for economic development through taxation, public borrowing, public enterprises, deficit financing and foreign aid.
Keywords: Nepal -economic policy